Analisis Spasial Perubahan Tutupan Lahan terhadap Suhu Permukaan di Kota Malang - Komura, Al Ikhsan Rama; Khalidy, Diky Al; Gastama, Aulia Nindy Fadila; Nuryadin, Muhammad Taufan; Hidayati, Widya Nur; Maghfiroh, Ainun; Bachri, Syamsul (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
This study aims to analyze the impact of land cover changes on land surface temperature LST in Malang City for the years 2015 2019 and 2024 using geospatial technology The methods include supervised classification for land cover analysis and LST extraction using Sentinel 2 and Landsat 8 imagery The results show a significant increase in built up areas from 5 793 ha 2015 to 8 419 ha 2024 while vegetated areas declined sharply from 3 952 ha to 2 356 ha during the same period Surface temperatures rose from 28 4 C 2015 to 30 2 C 2024 indicating a negative correlation between NDVI and LST R = 0 5521 in 2024 The decline in vegetation due to urbanization contributes to rising surface temperatures This study recommends sustainable land management policies through environmentally friendly regional spatial planning< em>< p>